2022
DOI: 10.1007/s00128-022-03460-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urban Green Spaces on Reduction of Particulate Matter Concentration

Abstract: In an urban scenario, one of the air pollutants most harmful to human health and environmental is the particulate matter (PM). Considering that urban green areas can contribute to mitigating the effects of PM, this work compares the concentration of PM 2.5 in two closer locations in Rio de Janeiro, in order to verify how vegetation cover can actually improve air quality. One is the entrance to the Rebouças Tunnel (RT) and the other is the Rio de Janeiro Botanical Garden (RJBG). For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…For instance, residents of these neighborhoods tend to engage more in physical activity [23]. Moreover, living in green spaces might improve mental health and reduce detrimental environmental exposures to air pollutants, noise, and heat [24,25]. In our study, we observed a connection between the density of green areas and a decrease in HF-related hospitalizations [26].…”
Section: Discussionsupporting
confidence: 49%
“…For instance, residents of these neighborhoods tend to engage more in physical activity [23]. Moreover, living in green spaces might improve mental health and reduce detrimental environmental exposures to air pollutants, noise, and heat [24,25]. In our study, we observed a connection between the density of green areas and a decrease in HF-related hospitalizations [26].…”
Section: Discussionsupporting
confidence: 49%
“…In the management strategy, extensification of greenspace is a land cover method of any landscape to reduce evaporation (46) and treat aerosol (47,48). The existence of greenspace is proven, among others, to be able to move gas the air to the vegetation area (49,50).…”
Section: Canopy Extensionmentioning
confidence: 99%
“…Many researchers have found that green open space in cities is essential in reducing air pollution. Junior et al (2022) suggest that urban green areas can reduce particulate levels compared to places with less vegetation cover, providing better air quality. The mechanism for reducing such pollutants is particle deposition, dispersion, and modification (Diener and Mudu 2021).…”
Section: Resultsmentioning
confidence: 99%